Evidence-Informed Decision-Making Training in Child Welfare: Evaluation of a Proof of Concept. Issue 4 (4th July 2022) - Lwin, Kristen; Laryea, Ahiney; Walker, Hillary; Elgie, Christine; Head, Sarah; Gizzarelli, Rocco
ABSTRACT: Purpose: Child welfare organizations serve vulnerable families and are required to effectively address the system's dual mandate. Therefore, workers must understand how families' unique challenges may impact caregiver's parenting ability and how to mitigate these concerns. In turn, workers require a framework for service that will address clinical factors and reduce decision-making noise. Evidence-informed decision-making (EIDM) offers a comprehensive framework that guides child welfare workers through the service process. Method: This study provides the evaluation of an EIDM training ( n = 100) aimed at promoting attitudes and use of research of child welfare workers. This is a quantitative study that utilized pre- and posttest surveys to measure attitudes and behaviors related to EIDM. Results: Findings suggest that attitude toward and likelihood to adopt EBP, confidence in using research, and perceived barriers to utilizing research significantly improved over the course of the five-month training. Discussion: Findings suggest that key participant characteristics can be improved following education. Indeed, there are many factors, including organizational, that contribute to whether EIDM is utilized in the field. Workers, however, must be knowledgeable and feel confident about the use of EIDM in everyday practice for there to be a successful implementation and sustained use in practice.